2017
DOI: 10.1002/ps.4670
|View full text |Cite
|
Sign up to set email alerts
|

Aerial release of Rhinoncomimus latipes (Coleoptera: Curculionidae) to control Persicaria perfoliata (Polygonaceae) using an unmanned aerial system

Abstract: BACKGROUND: Rhinoncomimus latipes (Coleoptera: Curculionidae) is a major biological control agent against the invasive plant Persicaria perfoliata. Release of R. latipes is challenging with the current visit-and-hand release approach because P. perfoliata shows a high degree of patchiness in the landscape, possesses recurved barbs on its stems, and often spreads into hard-to-access areas. This 3-year study developed and evaluated unmanned aerial systems (UAS) for precise aerial release of R. latipes to control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 27 publications
(52 reference statements)
0
7
0
Order By: Relevance
“…UAS have been increasingly utilized for various agricultural applications, such as crop and soil monitoring [ 31 , 32 , 33 , 34 , 35 ], pest detection [ 3 , 36 ], aerial releases of natural enemies [ 7 , 37 ], and pesticide application [ 38 ]. With the availability of small rotary-wing UAS equipped with high-resolution cameras, it is now possible to detect insects directly from aerial images [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…UAS have been increasingly utilized for various agricultural applications, such as crop and soil monitoring [ 31 , 32 , 33 , 34 , 35 ], pest detection [ 3 , 36 ], aerial releases of natural enemies [ 7 , 37 ], and pesticide application [ 38 ]. With the availability of small rotary-wing UAS equipped with high-resolution cameras, it is now possible to detect insects directly from aerial images [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that a major cost of using a small UAS for insect outbreak surveys was fees for the use of technology, including UAS and image analysis. As the price of such technology has decreased with technological advances [ 7 ] the use of UAS and image analysis could be cheaper in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multi-copters, including commonly used platforms such as quadcopters, hexacopters, octocopters, or their variants, are popular as base aerial platforms for many civilian applications, including remote sensing [1][2][3], aerial imaging [4,5], firefighting [6,7], environmental measurement [8][9][10], law enforcement [11][12][13], disaster relief and emergency management [14][15][16][17][18], situational awareness [19] infrastructure surveys [20], and several other military and commercial applications. Quadcopters can be considered to be representative of this general class of aircraft, and can be maneuvered by varying the power of the four motors symmetrically or asymmetrically in order to achieve translational and rotational flight.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, recent technical trends, including minimization of high-quality sensors, have led to new possibilities in the use of unmanned aerial systems (UAS) in various fields and applications [20]. In particular, UAS are now used in ecology and agriculture in a spectrum of research topics [20,21], such as plant identification [22] and weed management [23,24], or pest control and insect monitoring [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%